2016
DOI: 10.5888/pcd13.150564
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarette Use Among High School Students and Its Association With Cigarette Use And Smoking Cessation, North Carolina Youth Tobacco Surveys, 2011 and 2013

Abstract: IntroductionAlthough adolescent cigarette use continues to decline in the United States, electronic cigarette (e‑cigarette) use among adolescents has escalated rapidly. This study assessed trends and patterns of e‑cigarette use and concurrent cigarette smoking and the relationships between e-cigarette use and smoking cessation intentions and behaviors among high school students in North Carolina.MethodsData came from high school students who completed the school-based, cross-sectional North Carolina Youth Toba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 30 publications
(34 reference statements)
3
20
0
Order By: Relevance
“…In fact, nearly 60% of current youth combustible cigarette smokers surveyed in the NCYTS reported that they were attempting to quit smoking [24]. While recent studies of North Carolina youth have suggested that adolescents are perhaps less likely than adults to use e-cigarettes as part of an attempt to quit using tobacco products altogether [2], it is possible that a portion of the rise in e-cigarette use among youth may represent their attempt to mimic their parents' and peers' use of this more socially acceptable use of tobacco products. Moreover, our findings revealed a correlation based on ascending grade level between a perception of decreased risk of e-cigarette use and an increasing prevalence of lifetime use of e-cigarettes.…”
Section: Combustible Cigarette Use and Selfperceived Riskmentioning
confidence: 99%
“…In fact, nearly 60% of current youth combustible cigarette smokers surveyed in the NCYTS reported that they were attempting to quit smoking [24]. While recent studies of North Carolina youth have suggested that adolescents are perhaps less likely than adults to use e-cigarettes as part of an attempt to quit using tobacco products altogether [2], it is possible that a portion of the rise in e-cigarette use among youth may represent their attempt to mimic their parents' and peers' use of this more socially acceptable use of tobacco products. Moreover, our findings revealed a correlation based on ascending grade level between a perception of decreased risk of e-cigarette use and an increasing prevalence of lifetime use of e-cigarettes.…”
Section: Combustible Cigarette Use and Selfperceived Riskmentioning
confidence: 99%
“…Consequently, initial growth in the prevalence of use of these products was noted among cigarette smokers 3. Over time, however, extensive marketing,4 improvements in design, extensive flavor options,5 and a widespread perception that e‐cigarettes were safer than cigarettes led to their increased popularity, especially among youth6, 7, 8, 9, 10 and those who never smoked tobacco 9, 10. This increasing popularity has raised public health concerns, given the paucity of high‐quality longitudinal evidence on the health effects of e‐cigarette exposure and uncertainly about the data supporting their use as smoking‐cessation devices 1…”
Section: Introductionmentioning
confidence: 99%
“…About 5% of college students who have never smoked are using e-cigs (6). Fifty percent of adult smokers in the US have tried e-cigs, and 23% currently use both cigarettes and e-cigs (termed dual users) (5, 79). For adults and youth who use multiple tobacco products, the most common combination is cigarettes and e-cigs (5).…”
Section: Introductionmentioning
confidence: 99%